The effect of ionic strength on the structural organization of dioctadecyldimethylammonium bromide in aqueous solution - Feitosa, E.; Barreleiro, PCA (Springer, 2004)
High-curvature and stabilized vesicles of dioctadecyldimethylammonium bromide (DODABr) can be formed spontaneously in aqueous electrolytic solution. It is shown by cryo-transmission electron microscopy that 5.0 mM DODABr molecules associate in water at a temperature above its gel-to-liquid-crystalline phase transition temperature (T(m)approximate to45 degreesC) in a variety of complex bilayer structures. However, in the presence of NaCl the preferred structures formed are unilamellar and bilamellar vesicles with high curvature and the dispersion is polydisperse in size and geometry, but the main vesicle population contains spherical, flattened and smoothed structures. It is, however, less polydisperse than the corresponding salt-free dispersion, and the size polydispersity and the vesicle curvature radius tend to decrease with NaCl concentration. Long cylindrical bilamellar vesicles, with a very thin water layer separating the bilayers are also formed in the presence of 10 mM NaCl. The effect of the ionic strength on T-m, obtained by differential scanning calorimetry, is shown to depend on the nature of the counterion: Br- decreases, whereas Cl- increases Tm of DODABr, indicating different affinity of these counterions for the vesicle surfaces.
Keywords: cryo-transmission electron microscopy; micro differential scanning calorimetry; Cationic vesicle; vesicle curvature; gel-to-liquid-crystalline phase transition temperature